Hyponatremia in Neurosurgical Patients - О. A. Beylerli; A. A. Bukhvostov (Креативная хирургия и онкология)
Hyponatremia refers to a common and potentially dangerous electrolyte imbalance observed in neurosurgical patients, particularly following traumatic brain injuries, subarachnoid hemorrhages, brain tumors, and pituitary surgeries. The paper discusses primary causes and pathophysiology of hyponatremia, including the syndrome of inappropriate secretion of antidiuretic hormone, central adrenal insufficiency, and cerebral salt wasting syndrome. The paper presents differential diagnostic approaches for accurately identifying the underlying causes of hyponatremia, as well as therapeutic strategies that include hypertonic sodium solution infusions, hydrocortisone replacement therapy, and the use of vasopressin receptor antagonists. The study delineates the potential complications associated with overly rapid correction of sodium levels, such as osmotic demyelination syndrome. It emphasizes the importance of accurate diagnosis and timely treatment to enhance patient outcomes and minimize the risk of complications.